THE EFFECTIVENESS OF JERUJU PLANT EXTRACT (ACANTHUS ILICIFOLIUS) AS ANTICANCER: LITERATURE REVIEW - Aziza Vira Arunita; Heni Setyowati Esti Rahayu; Prasojo Pribadi (Gaster, 2023)
One of the plants that live in Indonesia and has many benefits is Acanthus ilicifolius or jeruju. The jeruju plant is included in the Acanthus family plant which is used for traditional medicine. One of the benefits of the jeruju plant is as an anticancer. The literature search process related to Acanthus ilicifolius and anticancer was carried out using an electronic data base. The purpose of this literature review is to determine the effectiveness of jeruju plant extracts as anticancer and research methods used in previous studies. Jeruju plant extract can be used as an anticancer and has the potential to inhibit the proliferation of HeLa cervical cancer cells. In jeruju leaf extract contained flavonoids, saponins and terpenoids as anticancer compounds with cytotoxic activity values in isolates showed an IC50 value of 88.89 ug/mL. The test method is MMT with maceration extraction method and methanol solution.